Biomedical Polymers and Polymer Therapeutics - Chiellini, Emo.; Sunamoto, Junzo.; Migliaresi, Claudio.; Ottenbrite, Raphael M.; Cohn, Daniel. (Springer US, 2002)
Proceedings of the Third International Symposium on Frontiers in Biomedical Polymers including Polymer Therapeutics: From Laboratory to Clinical Practice, held May 23-27, 1999, in Shiga, Japan. This book focuses on the progress and unique discoveries in the interdisciplinary scientific and technological area of biomedical application of polymers. The topics include polymeric materials for biomedical and pharmaceutical applications, as well as polymeric materials in therapeutics.